Timescales of methane seepage on the Norwegian margin following collapse of the Scandinavian Ice Sheet - Cremiere, Antoine; Lepland, Aivo; Chand, Shyam; Sahy, Diana; Condon, Daniel J.; Noble, Stephen R.; Martma, Tõnu; Thorsnes, Terje; Sauer, Simone; Brunstad, Harald (Nature Communications, 2016)
Source: doi:10.1038/ncomms11509 Gas hydrates stored on continental shelves are susceptible to dissociation triggered by environmental changes. Knowledge of the timescales of gas hydrate dissociation and subsequent methane release are critical in understanding the impact of marine gas hydrates on the ocean–atmosphere system. Here we report a methane efflux chronology from five sites, at depths of 220–400 m, in the southwest Barents and Norwegian seas where grounded ice sheets led to thickening of the gas hydrate stability zone during the last glaciation. The onset of methane release was coincident with deglaciation-induced pressure release and thinning of the hydrate stability zone. Methane efflux continued for 7–10 kyr, tracking hydrate stability changes controlled by relative sea-level rise, bottom water warming and fluid pathway evolution in response to changing stress fields. The protracted nature of seafloor methane emissions probably attenuated the impact of hydrate dissociation on the climate system.